2022
DOI: 10.3390/cmd3040038
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Radiolysis Issues in Water-Cooled Fission and Fusion Reactors: Part II, Prediction of Corrosion Damage in Operating Reactors

Abstract: The radiolysis of water is a significant cause of corrosion damage in the primary heat transport systems (PHTSs) of water-cooled, fission nuclear power reactors (BWRs, PWRs, and CANDUs) and is projected to be a significant factor in the evolution of corrosion damage in future fusion reactors (e.g., the ITER that is currently under development). In Part I of this two-part series, we reviewed the proposed mechanisms for the radiolysis of water and demonstrate that radiolysis leads to the formation of a myriad of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…The concentrations of the major radiolysis products (H 2 , O 2 , and H 2 O 2 ) were used to estimate the ECP and CGR for IGSCC in sensitized Type 304 SS and, to the authors' knowledge, Macdonald et al [216,218] were the first to have calculated the ECP and CGR using the MPM [217] and the CEFM [225], respectively. The CGR was then used to estimate the accumulated corrosion damage (crack length vs. time) as the reactor moves along the corrosion evolutionary path (CEP) [216,[225][226][227][228][229][230][231][232][233][234][242][243][244], as discussed in detail in Part II [291]. These same calculations should be made for ITER because they provide a rational basis for specifying the optimal water chemistry protocol for minimizing corrosion damage and activity transport.…”
Section: Nomentioning
confidence: 99%
See 4 more Smart Citations
“…The concentrations of the major radiolysis products (H 2 , O 2 , and H 2 O 2 ) were used to estimate the ECP and CGR for IGSCC in sensitized Type 304 SS and, to the authors' knowledge, Macdonald et al [216,218] were the first to have calculated the ECP and CGR using the MPM [217] and the CEFM [225], respectively. The CGR was then used to estimate the accumulated corrosion damage (crack length vs. time) as the reactor moves along the corrosion evolutionary path (CEP) [216,[225][226][227][228][229][230][231][232][233][234][242][243][244], as discussed in detail in Part II [291]. These same calculations should be made for ITER because they provide a rational basis for specifying the optimal water chemistry protocol for minimizing corrosion damage and activity transport.…”
Section: Nomentioning
confidence: 99%
“…The features described above have, in general, been predicted and observed for all fourteen BWRs that have been modeled in our group over the past three decades, with only relatively minor differences between different reactors. In Part II of this review [291], data of the type shown in Figures 13-15 are used to predict the ECP and CGR for IGSCC in sensitized Type 304 SS in operating plants. It is shown that HWC can have a significant impact on the mitigation and the accumulation of IGSCC damage in certain locations (e.g., RS, LP) but not in others (e.g., UD) and that the reasons for the differences are well understood in terms of the electrochemistry of the system.…”
Section: Nomentioning
confidence: 99%
See 3 more Smart Citations